Time-Induced Stress Effect on Financial Decision Making in Real Markets: The Case of Traffic Congestion - Sergey Gelman; Doron Kliger (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We study the role of stress induced by time constraints on investors' decision making. The need to perform contemporaneous tasks and external interference such as arriving unexpectedly late to work, might exacerbate acute stress and its impact on decision making. Accumulated laboratory research suggests that time stress may impact financial decisions, mainly in the loss domain. We contribute to the literature studying this issue in real financial markets, as the real markets distinguish themselves from laboratory experiments through repeated situations, aggregation of outcomes and extremely high monetary stakes. We use data on traffic congestion, weather conditions and derivative prices. Our main dependent variable is the slope of the implied volatility function (IVF) of options on RTS futures (cf. Bollen and Whaley, 2004) at the left-hand side of the volatility smile. We find that, controlling for relevant factors, this slope at open of the main trading session is higher subsequent to morning traffic jams, suggesting that investors under stress assign higher weights to extreme loss scenarios.
Keywords: G02; G13; G14; 330